2014
DOI: 10.1097/acm.0000000000000088
|View full text |Cite
|
Sign up to set email alerts
|

An Anthropological Approach to Teaching Health Sciences Students Cultural Competency in a Field School Program

Abstract: International immersion experiences do not, in themselves, provide students with the opportunity to develop cultural competence. However, using an anthropological lens to educate students allows them to learn how to negotiate cultural differences by removing their own cultural filters and seeing events through the eyes of those who are culturally different. Faculty at the University of Wisconsin-Madison's Global Health Institute believed that an embedded experience, in which students engaged with local communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…Our findings about the positive impact of involvement of faculty and trainees are consistent with medical education literature, which emphasizes the importance of mentorship as an opportunity to model professionalism, humanism, and ethical and cultural humility. [15][16][17][18] Our program evaluation is strengthened by inclusion of a subgroup of students surveyed after their elective to determine whether the PDO adequately prepared them for their experiences. This survey confirmed the benefits of the PDO and showed that all students, regardless of prior global health experience, perceived these benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings about the positive impact of involvement of faculty and trainees are consistent with medical education literature, which emphasizes the importance of mentorship as an opportunity to model professionalism, humanism, and ethical and cultural humility. [15][16][17][18] Our program evaluation is strengthened by inclusion of a subgroup of students surveyed after their elective to determine whether the PDO adequately prepared them for their experiences. This survey confirmed the benefits of the PDO and showed that all students, regardless of prior global health experience, perceived these benefits.…”
Section: Discussionmentioning
confidence: 99%
“…This set-up creates a reliable, efficient programme that is more likely to succeed over time. One of the studied health science programmes makes use of a third party person who is local to the community, which has shown to help build legitimacy and strong networks between the programme participants and host community [18]. This person can also help student integration into the community and can bridge cultural gaps to aid with immersion [19].…”
Section: Homestay Characteristicsmentioning
confidence: 99%
“…Homestays allowed these students the level of immersion that made it possible for them to more fully understand the complexities of lifestyle and disease and the challenges of global health [19]. A second study of health science field courses found that 91% of students who lived in homestays while serving the community report using cross-cultural skills in their health career while 63% use their language skills, which are both largely attributed to the immersive living experience [18]. Health science students also report that they believe an immersive experience should be a required part of their education, showing their support for these programmes [18].…”
Section: Homestay Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Furthermore, involvement in the community fosters partnerships that result in sharing and maximizing resources and helps children develop healthy behaviors while promoting healthy families. These partnerships also directly benefit the medical schools; community involvement directly predicts the degree to which academic institutions engage community members in their studies 2 , something that most faculty agree enhances the relevance of their clinical research.…”
mentioning
confidence: 99%